LEGALITAS SUMPAH COR “THE DECISSOIR OF THE TRUTH FOR BALINESE’S HINDUISM” DALAM SISTEM HUKUM ACARA PERDATA INDONESIA - I Wayan Sudarma (Maha Widya Bhuwana: Jurnal Pendidikan, Agama dan Budaya, 2020)
This article contains about how efforts to resolve disputes for the Hindu’s community refers to local wisdom based on Hinduism. In addition to legal references for Hindu society over civil issues, this paper is expected to be able to open people's understanding that, not all disputes can be resolved through the trial process which will certainly have an impact on the potential for new problems in the future. As for solutions that have no potential for new legal issues but have an impact on proving the truth in the perspective of Hinduism, one of which is, ‘Sumpah Cor’ (oath of cor) as the decissoir of the truth for Balinese’s Hinduism.